Capacity assessment for provision of quality sexual reproductive health and HIV-integrated services in Karamoja, Uganda. - Marotta, Claudia; Lochoro, Peter; Pizzol, Damiano; Putoto, Giovanni; Mazzucco, Walter; Saracino, Annalisa; Monno, Laura; Di Gennaro, Francesco; Ictho, Jerry (African Health Sciences, 2020)
Introduction: Sexual and reproductive health (SRH) and Human Immunodeficiency Virus (HIV) are crucial global health issues. Uganda continues to sustain a huge burden of HIV and AIDS. Methods: A cross-sectional health facility-based assessment was performed in November and December 2016 in Karamoja Region, northern Uganda. All the 126 health facilities (HFs) in Karamoja, including 5 hospitals and 121 Health Centers (HCs), covering 51 sub-counties of the 7 districts were assessed. We assessed the capacity of a) leadership and governance, b) human resource, c) service delivery, d) SRH and HIV service integration and e) users satisfaction and perceptions. Results: 64% of the established health staffing positions were filled leaving an absolute gap of 704 units in terms of human resources. As for service delivery capacity, on 5 domains assessed, the best performing was basic hygiene and safety measures in which 33% HCs scored “excellent”, followed by the presence of basic equipment. The level of integration of SRH/HIV services was 55.56%. Conclusion: HFs in Karamoja have capacity gaps in a number of health system building blocks. Many of these gaps can be addressed through improved planning. To invest in improvements for these services would have a great gain for Uganda.
Keywords: HIV-Integrated Services; Karamoja; Quality Sexual Reproductive Health; Uganda